2013
DOI: 10.1007/s00392-013-0611-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trimetazidine in patients with acute myocardial infarction: data from the Korean Acute Myocardial Infarction Registry

Abstract: Trimetazidine appeared to improve clinical outcomes in AMI patients by significantly reducing all-cause mortality and MACE over 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
1
15
0
10
Order By: Relevance
“…TMZ, an antianginal drug, protects ischemic cardiomyocytes by restoring their ability to produce energy, and has been widely used to treat various cardiovascular diseases such as coronary heart disease and heart failure [24,25]. In basic medical science, TMZ has been demonstrated to have pleiotropic effects.…”
Section: Discussionmentioning
confidence: 99%
“…TMZ, an antianginal drug, protects ischemic cardiomyocytes by restoring their ability to produce energy, and has been widely used to treat various cardiovascular diseases such as coronary heart disease and heart failure [24,25]. In basic medical science, TMZ has been demonstrated to have pleiotropic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that TMZ exerts cardioprotective effects in the setting of myocardial ischemia, including acute myocardial infarction [8,9]. It was reported that daily use of TMZ (20 mg, three times a day) for 5 ± 2 days before coronary angiography and a loading dose of 60 mg 30 min before percutaneous coronary intervention (PCI) could significantly reduce the frequency of angina pectoris attacks and myocardial damage during PCI, and improve left ventricular function during follow-up after PCI [10].…”
Section: Introductionmentioning
confidence: 99%
“…From an initial set of 156 nonduplicate records, a total of 7 clinical studies were finally included in the meta-analysis [13,14,15,16,17,18,19]. The characteristics of these included studies are detailed in table 1, and the results of the modified Newcastle-Ottawa assessment scale quality assessment of these included studies are detailed in table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The retrospective analysis by Kim et al [13] of acute MI patients revealed that adjunctive trimetazidine therapy reduced the all-cause mortality risk by 59% and that of total MACE by 76% over a 12-month follow-up period. Moreover, the prospective study of Shehata [19] on diabetic acute MI patients revealed that adjunctive trimetazidine therapy was associated with reduced myocardial damage, earlier reperfusion, amelioration of left ventricular ejection fraction, and lower total MACE.…”
Section: Discussionmentioning
confidence: 99%